GAMBARAN ALTRUISME PADA SATGAS PPKS MAHASISWA DI KOTA LHOKSEUMAWE - Annisa Arifatuwilma; Ella Suzanna; Zurratul Muna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The PPKS Task Force is part of a university that functions as a center for the prevention and handling of sexual violence that occurs in universities. This study aims to determine the description of altruism in PPKS Task Force students in Lhokseumawe City seen from their characteristics. This study uses a qualitative research method with a phenomenological approach. In this study, there were three subjects with the criteria of subjects, namely active students who are members of the PPKS Task Force of universities and have handled cases. The results of this study describe altruism in PPKS Task Force members of student elements. In the characteristics of empathy, it is obtained that the third subject generally positions himself as a victim in order to provide maximum assistance. In the characteristics of believing in world justice, it is obtained that the third subject will try his best and even ignore the existing risks, in order to provide justice to the victim. In the characteristics of social responsibility, it is obtained that the third subject feels that he must be responsible for the difficulties experienced by people around him. Then in internal self-control, the third subject shows that their desire to help victims comes from within themselves, they feel satisfied when they succeed in helping victims. Then, in the low ego characteristics, the third subject showed an attitude that prioritizes the interests of the victim over his own interests.